Case report: Multiple arterial stenoses induced by autosomal-recessive hypophosphatemic rickets type 2 associated with mutation of ENPP1: a case study - Liu, Jie; Song, Xitao; Zhang, Daming; Jiang, Yan; Ma, Mingsheng; Qiu, Zhengqing; Xia, Weibo; Chen, Yuexin (Frontiers in Cardiovascular Medicine, 2023)
ENPP1-related multiple arterial stenoses is a rare clinical syndrome in which global arterial calcification begins in infancy, with a high probability of early mortality, and hypophosphatemic rickets develops later in childhood. The vascular status of an ENPP1-mutated patient when they entered the rickets phase has not been thoroughly explored. In this study, we presented the case of an adolescent with an ENPP1 mutation who complained of uncontrolled hypertension. Systematic radiography showed renal, carotid, cranial, and aortic stenoses as well as random calcification foci on arterial walls. The patient was incorrectly diagnosed with Takayasu arteritis, and cortisol therapy had little effect on reducing the vascular stenosis. As a result, phosphate replacement, calcitriol substitution, and antihypertensive medication were prescribed, and the patient was discharged for further examination. This research presented the vascular alterations of an ENPP1 mutant patient, and while there is less calcification, intimal thickening may be the primary cause of arterial stenosis.